Role of body fat distribution and the metabolic complications of obesity - Jensen, Michael D (The journal of clinical endocrinology and metabolism, 2008)
An upper body/visceral fat distribution in obesity is closely linked with metabolic complications, whereas increased lower body fat is independently predictive of reduced cardiovascular risk. The measured functions of different fat depots with regards to fatty acid storage and release in health and obesity were reviewed. The adverse effects of experimentally increasing free fatty acid (FFA) concentrations on liver, muscle, pancreatic beta-cell, and endothelial function were noted. The most dramatic abnormality in FFA metabolism is failure to suppress FFA concentrations/adipose tissue lipolysis normally in response to postprandial hyperinsulinemia. Upper body sc fat delivers the majority of FFA to the systemic circulation under postabsorptive and postprandial conditions. In upper body obesity, portal FFA concentrations resulting from both systemic and visceral adipose tissue lipolysis may be significantly greater than arterial FFA concentrations, exposing the liver to even greater amounts of FFA. Visceral fat also releases sufficient IL-6 to increase portal vein IL-6 concentrations, which can affect hepatic metabolism as well. Lower body, upper body sc, and visceral fat depots have unique characteristics with regards to fatty acid metabolism. Selective dysregulation of these depots probably plays an important role with the metabolic complications of obesity.